Daya Dukung Silvopastur di Kecamatan Insana Kabupaten Timor Tengah Utara Nusa Tenggara Timur - Naikofi, I.; Wijayanto, N.; Fuah, A. M. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2019)
Research on “Carrying capacity of silvopastur in Insana Subdistrict, North Central Timor Regency, East Nusa Tenggara” has been carried out from April to June 2018. This study aims to identify the types and availability of animal feed to analyze the strategy of developing cattle basel carrying capacity of silvopastur in Insana Regency. This research was conducted using survei method on secondary data collection. The analysis used was descriptive analysis and SWOT analysis. The results showed that (1) the types of forages found in three villages are: grass includes; alang-alang grass (Imperata cylindrica), field grass (Axonopus compressus) (b) leguminosa consisting of shy daughters (Mimosa pudica), and feed from food crops in the form of rice straw, corn straw, sweet potatoes, banana stems. (c) and several types of forages from forestry plants in the form of how manikin (Bauhinia purpurea), Kabesak (Vachellia leucophloea). (2) The highest potential area for developing ruminants is Manunain B village as much as 800 999.84 animal unit, with an increasing population capacity of 18.53%, and followed by Tapenpah Village with 457 358.94 animal unit with an increase capacity by 51.12%, while Sekon Village is still can accommodate 423 501.18 animal unit with an increase capacity of 30.33%.